Susceptibility to cardiac ischemia/reperfusion injury is modulated by chronic estrogen status. - Beer, S; Reincke, M; Kral, M; Lie, S; Steinhauer, S; Schmidt, H; Allolio, B; Neubauer, S (2002)
The purpose of this study was to test whether the susceptibility of the heart to ischemia/reperfusion injury is modulated by the chronic estrogen status, i.e., increased with estrogen deficiency and attenuated by pharmacologic estrogen supplementation. In addition, the study tested whether estrogen-dependent changes in mechanical function are associated with alterations of cardiac high-energy phosphate metabolism. Rats were ovariectomized, not ovariectomized, or ovariectomized and treated with subcutaneous estrogen pellets (1.5 mg/21 d) (n = 8-11 per group). Three weeks later, hearts were isolated and perfused isovolumically under constant perfusion pressure conditions. Hearts were subjected to 15 min of total global ischemia (37 degrees C) and 30 min of reperfusion. Simultaneous [31P] nuclear magnetic resonance spectra were recorded throughout this protocol to monitor changes in ATP, phosphocreatine, and inorganic phosphate content. Whereas preischemic values for heart rate, end-diastolic pressure, and coronary flow were not different among groups, left ventricular developed pressure was slightly but significantly decreased in the estrogen-treated group (p < 0.05). However, treated hearts showed improved recovery of left ventricular developed pressure on reperfusion (89 +/- 4% in control rats, 70 +/- 8% in ovariectomized hearts, and 114 +/- 9% of preischemic values in estrogen-treated rats). However, changes in ATP, phosphocreatine, and inorganic phosphate during ischemia were as previously described and were unaffected by chronic estrogen status. In conclusion, in the isolated buffer-perfused rat heart, estradiol treatment caused improved functional recovery after ischemia/reperfusion injury. This improvement, however, did not include preservation of high-energy phosphate metabolism. Other potential mechanisms include an anti-oxidant activity of 17beta-estradiol-and estrogen-induced alterations in glucose metabolism.